Emissions of isoprenoids from dominant tree species in subtropical China - Zeng, Jianqiang; Song, Wei; Zhang, Yanli; Mu, Zhaobin; Pang, Weihua; Zhang, Huina; Wang, Xinming (Frontiers in Forests and Global Change, 2022)
Emission factors (Es) are among major sources of uncertainties in regional or global emission estimates of biogenic volatile organic compounds (BVOCs). Tropical vegetation contributes approximately 70% of the global BVOC emissions, yet in-situ measurements of BVOC emissions from tropical tree species, especially naturally grown mature trees, are quite limited. In this study, BVOC emissions from twenty mature trees (15 evergreen broad-leaved and 5 evergreen needle-leaved) were measured using dynamic chambers, and the emitted BVOCs were collected using sorbent tubes and speciated with a thermal desorption-gas chromatography/mass spectrometry system (TD-GC/MS). Twenty BVOC compounds including isoprene, 14 monoterpene (MT) species and 9 sesquiterpene (SQT) species were quantified for calculating their Es. The results showed that Eucalyptus urophylla had the largest Es of isoprene (26.47±3.70 μg g-1 h-1) among all the measured trees, followed by Ficus hispida (20.74±1.78 μg g-1 h-1), Syzygium hainanense (20.49±1.36 μg g-1 h-1), Casuarina equisetifolia (18.70±2.91 μg g-1 h-1) and Mangifera indica (11.71±7.04 μg g-1 h-1). α-Pinene, β-pinene and limonene were the most abundant MTs, of which the largest Es were measured for Magnolia denudata (8.33±2.05 μg g-1 h-1), Castanopsis hystrix (5.29±3.24 μg g-1 h-1) and Magnolia denudata (3.11±1.07 μg g-1 h-1), respectively. The Es of SQT for the measured trees were lower than 0.50 μg g-1 h-1 except for Magnolia denudata (1.10±0.41 μg g-1 h-1). β-Caryophyllene was the most common SQT with Magnolia denudata having the highest β-Caryophyllene Es of 0.09±0.03 μg g-1h-1. The localized Es measured for dominant tree species could be used to update BVOC emission factors for typical vegetation types and help improve BVOC emission estimates in typical/subtropical regions and narrow their uncertainties.